2005
DOI: 10.1081/clt-53083
|View full text |Cite
|
Sign up to set email alerts
|

Does Ethanol Explain the Acidosis Commonly Seen in Ethanol-Intoxicated Patients?

Abstract: Ethanol intoxication is associated with acidosis, which does not correlate with BD or LAC. The complexity of pathogenesis of acidosis in ethanol intoxication justifies further diagnostic evaluation of these patients in order to rule out other causes of acidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In humans, ethanol consumption results in a mixed respiratory and metabolic acidosis and the blood pH is directly proportional to the blood ethanol concentration (Lamminpaa and Vilska, 1990, 1991; Zehtabchi et al, 2005). In this study, ethanol resulted in a mixed acidosis, a finding consistent with human clinical studies and previous reports from this laboratory where we have shown that with each bout of ethanol, the mother and the fetus were subjected to transient acidemia, irrespective of the period of gestation (Cudd et al, 2001b; Ramadoss et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, ethanol consumption results in a mixed respiratory and metabolic acidosis and the blood pH is directly proportional to the blood ethanol concentration (Lamminpaa and Vilska, 1990, 1991; Zehtabchi et al, 2005). In this study, ethanol resulted in a mixed acidosis, a finding consistent with human clinical studies and previous reports from this laboratory where we have shown that with each bout of ethanol, the mother and the fetus were subjected to transient acidemia, irrespective of the period of gestation (Cudd et al, 2001b; Ramadoss et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Perturbation in pH was hypothesized to be a mechanism underlying the teratogenic effects of ethanol even before FAS was described by Jones and colleagues (Horiguchi et al, 1971; Jones et al, 1973). Clinically, in humans, ethanol ingestion results in a mixed respiratory and metabolic acidosis and the blood ethanol concentration is directly proportional to the blood pH (Lamminpaa and Vilska, 1990, 1991; Sahn et al, 1975; Zehtabchi et al, 2005). In animal models of FASD, the mother and the fetus experience transient increases in arterial partial pressure of carbon dioxide (P a CO 2 ), resulting in a reduction in arterial pH (pH a ) with every bout of ethanol consumption (Cudd et al, 2001b; Ramadoss et al, 2006b; Ramadoss et al, 2007; West et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators have reported relationships between alcohol [16, 14, 12, 13] and cocaine intoxication [16, 17] and elevated initial lactate levels. Although these findings were not replicated in the current study, we did find a very strong relationship between THC use and elevated lactate levels with 15/16 (OR 15 95%CI 1.56– 693.14) patients who screened positive for THC having an elevated initial lactate level.…”
Section: Discussionmentioning
confidence: 99%
“…These reference ranges were determined by the manufacturer of this assay system and subsequently validated by independent in-house testing. Because of the reported association between common intoxicants such as alcohol[12–15] and cocaine [16, 17] and elevated lactate levels we also explored the association between common intoxicants (ethanol, cocaine, amphetamine, barbiturates, opiates, phenylcyclidine, benzodiazepines, and tetrahyrdocannabinol) and lactate levels using the results of serum ethanol levels and urine toxicology reports in the subset of patients for whom they were available.…”
Section: Methodsmentioning
confidence: 99%
“…We also wished to address the role of acidemia in alcohol-induced altered fetal cortical bone development, as alcohol exposure in human clinical cases is known to result in mixed respiratory and metabolic acidosis (Lamminpää and Vilska, 1990; 1991; Sahn et al, 1975; Zehtabchi et al, 2005). In animal models, acidemia has been described as a candidate mechanism for alcohol-induced developmental neuronal injury and altered amino acid homeostasis (Cudd et al, 2001; Horiguchi et al, 1971; Ramadoss et al, 2007; 2008b).…”
Section: Introductionmentioning
confidence: 99%